Scalable route to CH3NH3PbI3 perovskite thin films by aerosol assisted chemical vapour deposition. Issue 17 (31st October 2014) - Bhachu, D. S.; Scanlon, D. O.; Saban, E. J.; Bronstein, H.; Parkin, I. P.; Carmalt, C. J.; Palgrave, R. G.
Abstract : An industrially relevant, scalable deposition route to high quality MAPI films is reported. Abstract : Methyl-ammonium lead iodide is the archetypal perovskite solar cell material. Phase pure, compositionally uniform methyl-ammonium lead iodide thin films on large glass substrates were deposited using ambient pressure aerosol assisted chemical vapour deposition. This opens up a route to efficient scale up of hybrid perovskite film growth towards industrial deployment.